2021
DOI: 10.1108/bij-10-2020-0519
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of supply chain collaboration on supply chain visibility, stakeholder trust, environmental and financial performances: a partial least square approach

Abstract: PurposeThe need to stay competitive amidst ever-changing business environment has shifted competitive strategies from firms to supply chains. Managers are now basing competitive strategies on supply chains acknowledging that supply chains present competitive advantages among other resources. The purpose of the study is to explore the predictive relevance of supply chain collaboration and the extent to which it influences supply chain visibility, stakeholder trust, environmental and financial performances. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 47 publications
0
58
0
2
Order By: Relevance
“…To gain a competitive advantage, the companies have shifted their attention from firm-level to their supply chains. The supply chain collaboration positively influences the environmental as well as the financial performance of the organization (Baah et al , 2021). Cheon and Deakin (2010) also applied the concept of supply chain design and concluded that coordination and collaboration would enhance the sustainability level of business.…”
Section: Discussionmentioning
confidence: 99%
“…To gain a competitive advantage, the companies have shifted their attention from firm-level to their supply chains. The supply chain collaboration positively influences the environmental as well as the financial performance of the organization (Baah et al , 2021). Cheon and Deakin (2010) also applied the concept of supply chain design and concluded that coordination and collaboration would enhance the sustainability level of business.…”
Section: Discussionmentioning
confidence: 99%
“…This study specifically seeks to contribute to the literature by exposing how information sharing directly affects SMEs supply chain visibility, supply chain collaboration, supply chain agility and supply chain performance. In addition, the study further exposes the indirect roles of supply chain visibility, supply chain collaboration and supply chain agility on supply chain performance (Prakash et al , 2017; Baah et al , 2021a; Singh et al , 2021a). This study is relevant in that it contributes to knowledge on information sharing, supply chain visibility, supply chain collaboration, supply chain agility, supply chain performance and how these variables interact directly and indirectly.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Bellini et al [3] demonstrated the positive relationship that exists between collaborative experience and trust. On the other hand, Baah et al [28] found that collaboration helps to form trust within a supply chain, and Hameed and Naveed [29] also showed that collaborative activity between firms increases trust between firms. However, Kraus et al [8] found that trust between firms -promotes collaboration.…”
Section: Collaborative Activitymentioning
confidence: 99%